Assessment of health-related quality of life and patient's knowledge in chronic non-specific low back pain - Melinda Járomi; Brigitta Szilágyi; Anita Velényi; Eleonóra Leidecker; Bence László Raposa; Márta Hock; Petra Baumann; Pongrác Ács; Alexandra Makai (BMC, 2021)
Abstract Background Chronic non-specific low back pain syndrome (cnsLBP) is a severe health problem in developed countries, which has an important effect on patients' quality of life and is highly determined by socio-demographic factors and low back pain specific knowledge. We examined patients' health-related quality of life according to the results of the Short Form Health Survey (SF-36), low back pain knowledge (LBPKQ) and the social determinants of the participants. Methods We carried out our research in the first half of 2015 in Southern Transdanubia, Hungary. The examination included 1155 respondents living with chronic non-specific low back pain. The confidence interval of 95% was used, and the level of. significance was p < 0.05 using SPSS 22.0 software. Results The SF-36 questionnaire is suitable for the examination of patients' health-related quality of life (Cronbach's Alpha> 0.76), as the LBPKQ's Cronbach's Alpha was 0.726 also, which showed good validity. Longer-term disease meant a lower health-related quality of life (p < 0.05). A greater decrease of function (Roland Morris scores (RM)) accounts for a lower HRQoL and higher knowledge level. We found significant differences in LBPKQ scores according to sociodemographic parameters. The general health status was positively correlated with LBPKQ (p = 0.024) adjusted for demographic and pain and functional status. Conclusion The negative effect of the symptoms on patients' quality of life is proved, which is determined by different socio-demographic parameters furthermore by knowledge. Above all could be useful information for professionals to adopt the right interventions.